PENGARUH MODAL, JAM KERJA, DAN JUMLAH TENAGA KERJA TERHADAP PENDAPATAN PENGUSAHA UMKM BERBASIS KULINER DI KECAMATAN BANJARMASIN TIMUR - ADITYA PRAWIRA; SITI MUTMAINAH ZULFARIDATULYAQIN (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Aditya Prawira (2018) Effects of assets, operational hours and amounts of labours on the income of culinary-based Small Medium Enterprises (SME) in the sub-district of East Banjarmasin.Advisor: Dra. Hj. Siti Mutmainah Z, MT              This research was conducted to find out the characteristics of culinary-based SME in the East Banjarmasin sub-district, to find out whether assets, operational hours, amounts of workers simoultaniously and partially affected the income of culinary-based SME entrepreneurs in the sub-district of East Banjarmasin.            All the respondents in this research is all of owners of 22 culinary-based SMEs on the sub-district of East Banjarmasin. The research data’s was processed and analyzed using the multiple linear regression analysis method.The results the research showed that the of assets, operational hours and amounts of labours simoultaniously effected the income of the culinary-based Small Medium Enterprises (SME) in the sub-district of East Banjarmasin. Assets is the mos dominant variable that effected the income of the culinary-based Small Medium Enterprises (SME) in the sub-district of East BanjarmasinKeywords               : Income, assets, operational hours, amounts of         Labours